Development of soil radiocarbon profiles in a reactive transport framework. (1st August 2021) - Druhan, Jennifer L.; Lawrence, Corey R.
Abstract: Today, there is a greater appreciation for the importance of the physical protection of carbon (C) through interactions with mineral surfaces, isolation from microbes, and the important role of transport in shaping soil properties and controlling moisture limitations on decomposition. As our paradigm for soil organic carbon (SOC) preservation changes, so too should our representation of the underlying processes in soil models. Reactive transport models (RTMs) provide a framework capable of assessing the interactive influence of soil chemistry and transport processes on the accumulation and turnover of SOC. In this study, we present new developments in the isotopically enabled RTM "CrunchTope, " which is capable of explicitly tracking the three isotopes of carbon ( 12 C, 13 C, and 14 C) and their fractionation between multiple coexisting and interacting solid, liquid and gas phases. This modeling framework opens the door to new applications of depth-resolved RTMs models in application to SOC and deeper subsurface carbon reservoirs. Here, we demonstrate SOC accumulation and radiocarbon aging for long-timescale models of soil development in CrunchTope. Our goal is to assess advantages and limitations of such an approach and to identify the type and complexity of reaction networks that are required to adequately apply this model to SOC dynamics. We assess the behavior of this model relative to a high-resolution dataset of SOC content, stable isotope composition, and radiocarbon ages as well as physical and hydrologic data measured from a chronosequence of soils located near Santa Cruz, California. Starting from a previously published model using a simplified reaction network with a single class of carbon, we sequentially incorporate multiple C reservoirs subject to both reactivity and transport pathways. Our results indicate that multiple SOC pools with different mean ages of C do not inherently emerge as a result of including reactions which are conventionally expected to provide a diversity of transit times, i.e., sorption and complexation of SOC on mineral surfaces. Instead, transit times emerge as a result of the timescales of the reactions represented in the reaction network. For mineral associated C, the RTM framework imposes dynamic equilibrium with the fluid phase dissolved organic C, such that no distinction in radiocarbon ages is achieved between these pools. Aged C can be produced by including a solid-phase C reservoir, with a rate-limited solubilization coefficient. Aging of SOC in this way is more akin to selective preservation than to mineral protection and, while such a mechanism may be at play in many soils, mineral protection is thought to be at least as important. As such, our results indicate that additional parameterization is required to reproduce the heterogeneity of carbon transit times that result from organo-mineral interactions. These efforts show the promise of a modeling approach where the varied transit time of soil C emerges from the dynamic physical and hydrologic properties of the model rather than from the a priori assignment of operationally defined pools.